Identificação e monitoramento de regimes de escoamento em leito de jorro - Lourenço, Reimar de Oliveira (2006)
Spouted bed has been studied intensively because of its potential of application in several processes. Identification and characterization of flow regimes in spouted bed based on visual observation have been reported in literature. However, the characterization of flow regimes based on visual observation is not either usual or possible in industrial equipments. Therefore, the aim this thesis is to design an experimental apparatus dotted a data acquisition system in order to identify the flow regime of the spouted bed. The experimental data obtained from the experimental apparatus were compared with data obtained from simulation studies by using a computational fluid dynamic technique (CFD). Soybean and cotton seeds were used in this study. The spouted bed was build in stainless steel with the following dimensions: H = 85 cm, Dc = 21 cm, Di = 3.5 cm e θ = 60°. The pressure drop fluctuations in the bed were acquired on line by using the LabVIEW® 7.1 software. A 100 Hz sampling frequency was used in all runs. Graphical analysis of the pressure fluctuations versus time showed to be not appropriate for identification of the flow regimes. On the other hand, the use of the fast Fourier transform technique (FFT) over the pressure drop signals yielded a power spectrum. Based on this power spectrum it was possible to propose an effective identification criterion. By using this criterion it was possible to identify clearly all flow regimes in the bed: fixed, transition and spouting. Simulation results used for comparison with experimental data were obtained by using the commercial package FLUENT® 6.1.18. The porosity profiles and the characteristic curve of the spouted bed were calculated by using an Eulerian multiphase model. The comparisons showed a very good agreement between experimental and simulation results.